IDENTIFICATION OF THE STUDENTS' ATTITUDE TO PHYSICAL LESSON IN SMAN 8 JAMBI CITY - Tanti Tanti; Dwi Agus Kurniawan; Nur Ika Sandi Pratiwi (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:The students' attitude that occurs during the learning process is essential in directing human behavior. It shows the individual likes or dislikes a particular item. Students' attitudes in science subjects can be seen from how students respond to science subjects. This study aimed to determine how the students' attitude of SMAN 8 Jambi City towards Physics subjects. This research used quantitative research with a survey research design. The data collection technique used was a questionnaire with 5 points on the Likert scale. This research involved 174 students of SMAN 8 Kota Jambi. Data analysis in this study used descriptive statistics. The indicator used in this study was the attitude towards investigations in Physics. The analysis results obtained on indicator towards physics investigation was good with 64.4%.Abstrak:Sikap siswa yang terjadi selama proses pembelajaran sangat penting dalam mengarahkan perilaku manusia. Ini menunjukkan individu suka atau tidak suka item tertentu. Sikap siswa pada mata pelajaran IPA dapat dilihat dari bagaimana siswa merespon mata pelajaran IPA. Penelitian ini bertujuan untuk mengetahui bagaimana sikap siswa SMAN 8 Kota Jambi terhadap mata pelajaran Fisika. Penelitian ini menggunakan penelitian kuantitatif dengan desain penelitian survei. Teknik pengumpulan data yang digunakan adalah angket dengan 5 butir skala likert. Penelitian ini melibatkan 174 siswa SMAN 8 Kota Jambi. Analisis data dalam penelitian ini menggunakan statistik deskriptif. Indikator yang digunakan dalam penelitian ini adalah sikap terhadap investigasi Fisika. Hasil analisis yang diperoleh indikator terhadap investigasi fisika adalah baik dengan 64,4%.